3D Printing of A Thermally Programmable Conformal Metasurface. Issue 7 (10th January 2022) - Yin, Haoyu; Liang, Qingxuan; Duan, Yubing; Fan, Jun; Li, Zhaohui
Abstract: The curved surfaces conformality has become the coming barrier to the implementation of the metasurface carpet cloaks. A curved conformal strategy that can balance the electromagnetic performances and the manufacturing challenges of metasurface simultaneously is highly in demand, but yet underexplored. Herein, a novel thermal programming 3D‐printing method for curved conformal metasurface is proposed. Owing to the glass‐rubber transition characteristics of thermoplastic polymers, the advantages of rigid substrate and flexible substrate are fully utilized to achieve the conformality of metasurface, which ingeniously reduces the manufacturing complexity and ensures the electromagnetic performances. As a proof, an arched metasurface carpet cloak composed of the easy‐bending unit cells is designed and fabricated by the composite fused deposition molding of polylactic acid and Sn‐Bi materials with the thermal programming process. Experiments prove that the maximum reduced total radar cross section of the conformal cloak reaches about −9.4 dB while the 3 dB reduction bandwidth is ≈26.6%. The excellent cloaking performance of the metasurface sample demonstrates the effectiveness of this curved conformal method. This work provides a viable implementation strategy for complex curved metasurface and will substantially promote the applications of the conformal invisibility cloaks. Abstract : The conformality of curved surfaces has become the coming barrier to the implementation of metasurface‐based carpet cloaks. This work presents a curved conformal composite 3D printing method for metasurface based on the thermal programming of thermoplastic polymers' glass–rubber transition. Its effectiveness is adequately proved by the demonstration of an arched metasurface carpet cloak with excellent electromagnetic performances.